If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + by + c + 2ax + -3by + c + by + -1c = 0 Reorder the terms: ax + 2ax + by + -3by + by + c + c + -1c = 0 Combine like terms: ax + 2ax = 3ax 3ax + by + -3by + by + c + c + -1c = 0 Combine like terms: by + -3by = -2by 3ax + -2by + by + c + c + -1c = 0 Combine like terms: -2by + by = -1by 3ax + -1by + c + c + -1c = 0 Combine like terms: c + c = 2c 3ax + -1by + 2c + -1c = 0 Combine like terms: 2c + -1c = 1c 3ax + -1by + 1c = 0 Solving 3ax + -1by + 1c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'by' to each side of the equation. 3ax + -1by + by + 1c = 0 + by Combine like terms: -1by + by = 0 3ax + 0 + 1c = 0 + by 3ax + 1c = 0 + by Remove the zero: 3ax + 1c = by Add '-1c' to each side of the equation. 3ax + 1c + -1c = by + -1c Combine like terms: 1c + -1c = 0 3ax + 0 = by + -1c 3ax = by + -1c Divide each side by '3x'. a = 0.3333333333bx-1y + -0.3333333333cx-1 Simplifying a = 0.3333333333bx-1y + -0.3333333333cx-1
| 5=(7-2)/3-x | | 2x^2-13=7x | | 5=7-2/3-x | | 3(2star)-3star+4=2star+5 | | 4a+2b+c=8 | | 12-4(6x-2)=8-(2x+5) | | 35=5u | | 2x+6=7-3x | | 97=215t+-16t^2 | | y=sin(5x+2) | | 7w-16w= | | 6c=4c+6 | | 5(k-3)-8=5k-(4k-3) | | 4x+3-5x= | | 2x+80+145+x=360 | | -8g+4.5=36.3 | | 0.2(1.4-3x)+1.3x-2.9= | | c-d-5c+d= | | -3x-4=2(7x-4) | | 5+bx+3x=11 | | 9d^3=25 | | g(x)=-4x(x^2-16)(x-5) | | 11-4+8=4x+10 | | 2.91=24.444 | | 5x-6+2x=120 | | 5X(X+1)=2X+17 | | 5x+(x+1)=2X+17 | | 4u=25-3z | | 4-6cosx=8-2cosx | | 3x-6=4a+2x | | 3x(8-2)+4x-3= | | 4d+8=64 |